The interpretation of tax treaties in relation to domestic GAARs - Furuseth, Eivind, 1975- (Doctoral series ;, 2018)
There are more than 3,000 tax treaties in the world, and an important question is whether these tax treaties limit a state's ability to curb undesirable tax planning by the use of domestic general anti-avoidance rules (GAARs). Many large multinational companies use essentially legitimate methods to reduce taxes. Meanwhile, governments increasingly focus on the part of this tax planning that they view as undesirable; for example, tax planning schemes where income is shifted from one classification to another and/or shifted from one taxpayer to another. Although these transactions may be legitimate in principle, tax authorities may find that the tax planning scheme "stretches" the rules and thus wish to apply their domestic anti-avoidance rules. In order to decide whether a treaty restricts the use of domestic GAARs, the treaty must be interpreted. A basic principle in tax treaty law is that if the national rules are contrary to the treaty, the tax treaty prevails. A typical example is withholding tax on dividends: if the tax treaty provides for a lower withholding tax than what follows from domestic law, the treaty withholding tax rate prevails. A question that arises, however, is whether it is of any relevance, in terms of the relationship between tax treaties and domestic law, that the domestic tax rate is determined after the application of a domestic GAAR. This book argues that when State A and State B have agreed between themselves on how the taxation between these two countries should be shared, one of the contracting states may not, after the taxing right is shared, apply the domestic GAAR to override the tax treaty. Both domestic law and tax treaty law are under constant development. An important question is to what extent these developments affect the tax authorities' ability to counter undesirable tax planning. Is it true that tax agreements signed in recent years increasingly allow the tax authorities to apply their domestic anti-avoidance rules? This book demonstrates that it is of great importance when the tax treaty was signed for determining whether the tax authorities are restricted from using their domestic anti-avoidance rule to deny undesirable tax planning